Forensic anthropology theoretical framework and scientific basis - Boyd, C. Clifford Jr. 1952-; Boyd, Donna 1960- (Wiley, 2018)
"Provides comprehensive coverage of everything that students and practitioners need to know about working in the field of forensic anthropology"--Provided by publisher.